2001
DOI: 10.1523/jneurosci.21-09-03024.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection Mediated by Glial Cell Line-Derived Neurotrophic Factor: Involvement of a Reduction of NMDA-Induced Calcium Influx by the Mitogen-Activated Protein Kinase Pathway

Abstract: The glial cell line-derived neurotrophic factor (GDNF) is first characterized for its trophic activity on dopaminergic neurons. Recent data suggested that GDNF could modulate the neuronal death induced by ischemia. The purpose of this study was to characterize the influence of GDNF on cultured cortical neurons subjected to two paradigms of injury (necrosis and apoptosis) that have been identified during cerebral ischemia and to determine the molecular mechanisms involved. First, we demonstrated that both neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
142
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(143 citation statements)
references
References 54 publications
1
142
0
Order By: Relevance
“…We presume that sevoflurane induces preconditioning probably through activating this signal pathway, and our results confirm this hypothesis. MEK-ERK1/2 links growth factor receptors with nerve growth factor and brain-derived neurotrophic factor, to exert neuroprotective effects such as NMDA receptor modulation and reduction of glutamate excitotoxicity [29] . MEK-ERK1/2 also phosphorylates hypoxia-inducible factor 1, a transcription factor required for the cell adaptation to acute and chronic hypoxia [30] .…”
Section: Discussionmentioning
confidence: 99%
“…We presume that sevoflurane induces preconditioning probably through activating this signal pathway, and our results confirm this hypothesis. MEK-ERK1/2 links growth factor receptors with nerve growth factor and brain-derived neurotrophic factor, to exert neuroprotective effects such as NMDA receptor modulation and reduction of glutamate excitotoxicity [29] . MEK-ERK1/2 also phosphorylates hypoxia-inducible factor 1, a transcription factor required for the cell adaptation to acute and chronic hypoxia [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these neurotrophic factors are known to support neuronal survival and plasticity in various models of axonopathy and neuropathy. [42][43][44][45][46] Quantitative analysis of constitutive neurotrophic factor release from NSCs is relatively rarely reported in the literature, despite the popular theory that release of these proteins and their effects on compromised host tissue is a potential mechanism behind the cells' restorative capacity. 8,9,11,14,16 Time courses of release are generally lacking, as are release profiles from scaffolded cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we show that the MAPK pathway was required for axotomized RGC survival after GDNF treatment. Nicole et al 37 reported that GDNF reduces the conductance of the NMDA receptor through activation of the MAPK pathway, protecting cultured cells against glutamate excitotoxicity. This may be an additional MAPKdependent survival mechanism of GDNF after optic nerve transection.…”
Section: Discussionmentioning
confidence: 99%